GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 654 species occurrences available in GBIF matching the query: TaxonKey: Styela plicata (Lesueur, 1823) HasCoordinate: true HasGeospatialIssue: false. The dataset includes 654 records from 18 constituent datasets: 9 records from TCWC Marine Invertebrates. 1 records from Museum Victoria provider for OZCAM. 2 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 3 records from iNaturalist Research-grade Observations. 1 records from CSIRO, Cruise SS200510, Benthic Biodiversity, Western Australia, 2005. 345 records from NMNH occurrence DwC-A. 1 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1 records from Marine Biological Association - Marine Life Survey Data (collected by volunteers) collated by MarLIN. 10 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 1 records from Natural History Museum (London) Collection Specimens. 1 records from Akita Prefectural Museum＋Ascidians Specimens of Akita Prefectural Museum. 1 records from NBI. 117 records from North American Sessile Marine Invertebrate Survey. 3 records from Invertebrate Zoology Division, Yale Peabody Museum. 19 records from invertebratezoology. 4 records from South Western Pacific Regional OBIS Data All Sea Bio Subset (South Western P acific OBIS). 26 records from Queensland Museum provider for OZCAM. 109 records from Australian Museum provider for OZCAM.
Keywords: GBIF; biodiversity; species occurrences